Molecular features of bile salt hydrolases and relevance in human health - Chand, D.; Avinash, V. S.; Yadav, Y.; Pundle, A. V.; Suresh, C. G.; Ramasamy, S. (Biochimica et Biophysica Acta - General Subjects, 2017)
Background: Bile salt hydrolase (BSH) enzyme is responsible for the de-conjugation of bile salts by commensal bacteria, thus playing a vital role in their colonization and survival in the mammalian intestine and determination of their probiotic potential. Further, bile deconjugation also leads to lowering of cholesterol and alterations in energy homeostasis, thus making BSH a clinically important enzyme. Scope of the review: Many recent observations have indicated that BSH may be involved in a multifaceted array of roles, directly or indirectly in the host and microbial physiology. BSH paralogues have now been found to occur in different microbes including free-living and pathogenic bacteria and Archaea. BSHs from various sources also show differential activity and substrate spectrum. Certain bacteria are known to possess multiple genes for BSH enzymes. BSHs have been reported to influence different metabolic phenomena, including bacterial pathogenesis and the maintenance of lipid and glucose homeostasis in the host. These observations necessitate an intense study into the biochemical, structural and regulatory features of BSH enzymes to better understand their role in regulating bacterial and host metabolism. Major conclusions: In this review, the available information on the characteristics of BSH enzymes have been organized in order to understand their interactions with a wide range of substrates and their myriad physiological roles, from bile resistance to signalling mechanisms. General significance: A detailed exploration of BSH architecture and regulation could provide insights into its evolution and a deeper appreciation of the multiple functions of this enzyme relevant to healthcare.

Structure and function of a highly active Bile Salt Hydrolase (BSH) from Enterococcus faecalis and post-translational processing of BSH enzymes - Chand, D. (Biochim Biophys Acta., 2018)
Bile Salt Hydrolase (BSH), a member of Cholylglycine hydrolase family, catalyzes the de-conjugation of bile acids and is evolutionarily related to penicillin V acylase (PVA) that hydrolyses a different substrate such as penicillin V. We report the three-dimensional structure of a BSH enzyme from the Gram-positive bacteria Enterococcus faecalis (EfBSH) which has manifold higher hydrolase activity compared to other known BSHs and displays unique allosteric catalytic property. The structural analysis revealed reduced secondary structure content compared to other known BSH structures, particularly devoid of an anti-parallel β-sheet in the assembly loop and part of a β-strand is converted to increase the length of a substrate binding loop 2. The analysis of the substrate binding pocket showed reduced volume owing to altered loop conformations and increased hydrophobicity contributed by a higher ratio of hydrophobic to hydrophilic groups present. The aromatic residues F18, Y20 and F65 participate in substrate binding. Thus, their mutation affects enzyme activity. Docking and Molecular Dynamics simulation studies showed effective polar complementarity present for the three hydroxyl (-OH) groups of GCA substrate in the binding site contributing to higher substrate specificity and efficient catalysis. These are unique features characteristics of this BSH enzyme and thought to contribute to its higher activity and specificity towards bile salts as well as allosteric effects. Further, mechanism of autocatalytic processing of Cholylglycine Hydrolases by the excision of an N-terminal Pre-peptide was examined by inserting different N-terminal pre-peptides in EfBSH sequence. The results suggest that two serine residues next to nucleophile cysteine are essential for autocalytic processing to remove precursor peptide. Since pre-peptide is absent in EfBSH the mutation of these serines is tolerated. This suggests that an evolution-mediated subordination of the pre-peptide excision site resulted in loss of pre-peptide in EfBSH and other related Cholylglycine hydrolases.
Keywords: autocatalytic processing; Bile salt hydrolase; molecular dynamics; Mutagenesis; Polar complementarity; X-ray crystallography